ANALISIS BUDAYA KERJA TERHADAP KINERJA KARYAWAN PADA CV. TIGA SAUDARA - Andri Wijaya; Hesti Widi Astuti (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2015)
This study aims to determine the influence of culture on employee performance on CV. TigaSaudara, so it can be obtained the actual experience of the problems faced by CV. Tiga Saudaraand can be used as consideration to address the problems faced by CV. Tiga Saudara and efforts toachieve the objectives to be achieved by CV. Tiga Saudara.In this study, data analysis tool used is validity, reliability, simple linear regression, and t test.Methods of data collection was obtained from primary data sourced directly from employees whowork at CV. Tiga Saudara The results of the simple regression equation Y = 1,348 + 1,444X and ttest indicates that the variable of employee performance is influenced by culture variables.